An Overview of Cellular Network as A Sensor: From Mobile Phones Data to Real-time Road Traffic Monitoring (International Journal of Innovative Research in Computer Science & Technology, 2020)
Versatile cell organizations might go about  as pervasive actual portability sensors. Dependent just  upon anonymized flagging information assembled from a  versatile cell organization, we present a procedure for  surmising vehicle trip terms on interstates and identifying  gridlock continuously. Most earlier examinations utilized  information from cell phones that were occupied with  calls, like Call Detail Records (CDR), which limits the  number of apparent gadgets to a minuscule level of the  absolute populace. By utilizing the entire assortment of  flagging occasions created by both inactive and dynamic  gadgets, we can beat this defect. Dynamic gadgets offer  better grained geographic accuracy for a little part of  gadgets, while inactive gadgets give a colossal measure of  spatially coarse-grained portability information. Blockage  recognition execution is worked on as far as inclusion,  exactness, and idealness by joining information from  inactive and dynamic gadgets. People test our technique on  genuine portable flagging information from a functional  organization north of one month on an example parkway  section close to a European city and present an extensive  approval review because of ground truth got from an  assorted arrangement of reference information sources,  including street sensor information, cost information, taxi  drifting vehicle information, and radio station messages.
Keywords: Cellular Network; Congestion Detection; Mobility; Traffic Monitoring; Travel Time Estimation